Estratégia de fortificação alimentar (NutriSUS): percepção de gestores e profissionais de uma cidade do nordeste brasileiro - Sá, Lígia Araújo (2019)
The World Health Organization points to iron deficiency as one of the contributing factors to the decline in quality of life in the world. In Brazil, anemia is considered the most severe deficiency. In 2014, the NutriSUS Child Food Fortification Strategy with Powder Micronutrients was launched, aimed at enhancing the prevention and control of vitamin and mineral deficiencies in children, and was developed through joint work between public health and education services. Therefore, this research becomes relevant due to the lack of studies of this nature in João Pessoa - Paraíba, thus guiding the planning of local actions regarding the execution of the NutriSUS Strategy. The objective was to understand the perception of managers and health professionals about the development of the NutriSUS Strategy actions. This was an exploratory research with a qualitative approach, conducted from December 2018 to January 2019, from a semi-structured interview with 12 professionals, intentionally selected. The interviews were recorded, transcribed and analyzed through thematic content analysis, from which the following categories emerged: Understanding of managers and health professionals about the importance of the NutriSUS Strategy; Integration and articulation of Public Health and Education Networks in the NutriSUS Strategy; Operationalization of actions in the implementation of the NutriSUS Strategy. It was found that managers and health professionals had knowledge about the Strategy, which represents the desire of the Federal and Municipal governments. The planning of the actions of the NutriSUS Strategy followed the recommendations of the Health Department. However, the monitoring revealed weaknesses in its execution, with each professional performing their monitoring according to local availability, resulting in a weak communication process among professionals. In some territories, limitations were observed in the Intersectoriality process in the execution of the NutriSUS Strategy actions among the public health and education sectors. More intense pacts and actions aimed at intersectoral articulation are needed, as well as the improvement of actions that strengthen the communication link involving all actors connected to the implementation of the NutriSUS Strategy.